Working hours and life satisfaction: finding blind spots from Korean panel data. (2nd January 2021) - Lee, Hayoung
ABSTRACT: This study empirically tested the premise of working-hour reduction policies, which is that 'if working hours are reduced, the life satisfaction of employees will increase, ' and whether the effects of working hours on life satisfaction would differ according to employees' socioeconomic status, using longitudinal data from the Korean Labor and Income Panel Study for the period 2009–2017. We found that when working hours were reduced, work and leisure satisfaction increased significantly, but there was no significant increase in family or overall life satisfaction. In addition, when working hours decreased, the overall life, work, and leisure satisfaction of employees with higher socioeconomic status showed a significantly sharper increase than that of workers with lower socioeconomic status. These results imply that, in addition to current working-hour policies, additional efforts should be concentrated on employees who are not enjoying the policies' benefits sufficiently due to lack of resources other than time.